(EXPERIMENTAL VARIATION OF WATER HEAD AND DISCHARGE ON CROSS-FLOW TURBINE POWER - Muhammad Hasan Basri (Jurnal Teknik Mesin dan Pembelajaran, 2026)
Power plants in Indonesia are generally coal-fired steam power plants that still use fossil fuels whose availability is increasingly scarce. One category of water resource utilization as a promising renewable energy (electrical energy) is a pico-hydro power plant (PLTPH) that uses a cross-flow turbine system as a driving force. One effort to optimize turbine performance is by changing the turbine's operating parameters, namely water flow rate and head height. In this study, an experimental test will be conducted to determine the mechanical power performance of the turbine and the generator output power on the pump as a turbine produced by the turbine system by varying the flow rate and head in the cross-flow turbine system. The purpose of this study is to determine the effect of different flow rate and head variations on turbine power and generator power on the pump as a turbine. In this test, a specimen with an inlet angle of 30o and an outlet angle of 75o was used. The test specimen was made of composite material to be lighter and resistant to pressure. In the test installation, a frame was used to determine the falling water height of 3 meters, 4 meters, 5 meters and different flow rate variations. The largest generator power produced at a height of 5 meters and a water discharge of 0.00642 m³/second is 99.96 watts, at a generator shaft rotation of 881.4 rpm. The effect of variations in head height on generator power in cross flow turbines is directly proportional, with increasing head height, the generator power increases, the largest generator power is at a head height of 5 m with a generator force of 58.73 watts.